Filamentous fungi in Indah Water Konsortium (IWK) sewage treatment plant for biological treatment of domestic wastewater sludge - Fakhru’l-Razi, A.; Zahangir Alam, M.; Idris, Azni; Abd-Aziz, Suraini; Molla, Abul H. (Marcel Dekker, 2002)
A study was carried out to isolate and identify filamentous fungi for the treatment of domestic wastewater sludge by enhancing biodegradability, settleability and dewaterability of treated sludge using liquid state bioconversion process. A total of 70 strains of filamentous fungi were isolated from three different sources (wastewater, sewage sludge and leachate) of IWK's (Indah Water Konsortium) sewage treatment plant, Malaysia. The isolated strains were purified by conventional techniques and identified by microscopic examination. The strains isolated belonged to the genera of Penicillium, Aspergillus, Trichoderma, Spicaria and Hyaloflorae The distribution of observed isolated fungi were 41% in sewage sludge followed by 39% in wastewater and 20% in leachate. The predominant fungus was Penicillium (39 strains). The second and third most common isolates were Aspergillus (14 strains) and Trichoderma (12 strains). The other isolates were Spicaria (3 strains) and Hyaloflorae (2 strains). Three strains (WWZP1003, LZP3001, LZP3005) of Penicillium (P. corylophilum, P. waksmanii, and P. citrinum respectively), 2 strains (WWZA1006 and SS2017) of Aspergillus (A. terrues and A. flavus respectively) and one strain (SSZT2008) of Trichoderma (T. harzianum) were tentatively identified up to species level and finally verified by CABI Bioscience Identification Services, UK.